Teacher education - Panda, Bhujendra Nath.; Tewari, A. D., 1957-; Indian Association of Teacher Educators. Conference 1995 : Regional Institute of Education, Bhubaneswar) (New Delhi : A.P.H. Publishing Corporation, 1997)
Contributed papers of the 29th Annual Conference of the Indian Association of Teacher Educators, was organized from 23-25 December 1995, at Regional Institute of Education, Bhubaneswar.
Includes bibliographical references and index.
BIED
Complimentary copy from BIED
Keywords: Teachers -- Training of -- India -- Congresses